Household inflation expectations and inflation dynamics - Péter Gábriel (Magyar Nemzeti Bank, 2010)
Although in modern monetary economics it is usually assumed that inflation expectations play a prominent role when economic agents set prices and wages, the empirical evidence for this link is scarce. This paper aims to identify the effect of changes in inflation expectations on prices and wages in an sVaR framework for three inflation targeting countries (Czech Republic, Hungary and United Kingdom). The results show that in all countries the effect is significant. in comparison with the United Kingdom and the Czech Republic, inflation expectations in Hungary are more volatile and less anchored, which can be an important source of the high volatility of the inflation rate.
Keywords: C83; D84; E31; 330; inflation expectations; consumer survey; Inflationserwartung; Privater Haushalt; Inflationssteuerung; VAR-Modell; Tschechische Republik; Ungarn; Großbritannien